Dysfunction of the Mesolimbic Circuit to Food Odors in Women With Anorexia and Bulimia Nervosa: A fMRI Study - Jiang, Tao; Soussignan, Robert; Carrier, Edouard; Royet, Jean-Pierre (Frontiers in Human Neuroscience, 2019)
Brain reward dysfunction in eating disorders has been widely reported. However, whether the neural correlates of hedonic and motivational experiences related to food cues are differentially affected in anorexia nervosa of restrictive type (ANr), bulimia nervosa (BN) and healthy control (HC) participants remains unknown. Here, 39 women (14 ANr, 13 BN, and 12 HC) underwent fMRI while smelling food or non-food odors in hunger and satiety states during liking and wanting tasks. ANr and BN patients reported less desire to eat odor-cued food and odor-cued high energy-density food (EDF), respectively. ANr patients exhibited lower ventral tegmental area activation than BN patients to food odors when rating their desire to eat, suggesting altered incentive salience attribution to food odors. Compared with HC participants, BN patients exhibited decreased activation of the caudate nucleus to food odors in the hunger state during the wanting task. Both patient groups also showed reduced activation of the anterior ventral pallidum and insula in response to high EDF odors in the hunger state during the wanting task. These findings indicate that brain activation within the food reward-regulating circuit differentiates the three groups. ANr patients further exhibited lower activation of the precuneus than other participants, suggesting a possible role of body image distortion in ANr. Our study highlights that food odors are relevant sensory probes to gain better insight into the dysfunction of the mesolimbic and striatal circuitry involved in food reward processing in patients with EDs.